IMPLEMENTASI BAURAN PEMASARAN PADA BISNIS AYAM PETELUR AM FARM BALI - Ida Ayu Komang Tiara Pratistha Sari; Putu Ayu Diah Widari Putri; Nyoman Yudha Astriayu Widyari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
AM Farm is one of the egg-laying chicken businesses in Abiansemal District, Badung Regency, Bali and was established at the end of 2020 located in Br. Sukajati, Taman Village, Abiansemal District, Badung, Bali. The tight competition for egg-laying chickens has raised many questions for researchers about how to implement the marketing mix used by AM Farm in order to survive and compete in the increasingly rapid marketing world. The purpose of this researcher is to describe and implement the 7P marketing mix reviewed from the marketing mix aspect at AM Farm. The method used in this study is a descriptive method with a qualitative approach. The results of the study show that AM Farm implements a 7P marketing mix strategy which includes product, price, place, promotion, people, process, and physical evidence. Chicken eggs AM Farm produces red chicken eggs with 5 size categories, starting from pearl eggs (the smallest size available only when chickens are just starting/learning to lay eggs), small eggs, medium/regular eggs, large eggs, super/jumbo eggs. AM Farm determines prices through market price observations that are adjusted to market segmentation and based on the strategic level of the location. The promotional strategy used is word of mouth, direct marketing and social media. AM Farm has implemented its business until now because it can implement aspects of the marketing mix strategy and continues to innovate so that its business can grow and survive.